2010
DOI: 10.1007/s00264-010-0996-6
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis identifies distinct gene expression profiles associated with histological subtype in human osteosarcoma

Abstract: Osteosarcoma is the most common primary malignant bone tumour. Currently osteosarcoma classification is based on histological appearance. It was the aim of this study to use a more systematic approach to osteosarcoma classification based on gene expression analysis and to identify subtype specific differentially expressed genes. We analysed the global gene expression profiles of ten osteosarcoma samples using Affymetrix U133A arrays (five osteoblastic and five non-osteoblastic osteosarcoma patients). Different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 36 publications
0
33
0
2
Order By: Relevance
“…Earlier studies have similarly found clear downregulation of Wnt signalling in 25 high-grade prechemotherapy biopsies [36]. In many studies the comparisons are not made between healthy bone and osteosarcoma, therefore not all published gene expression-profiling studies are comparable with ours [37,38]. Therefore, some controversies exist about the involvement of Wnt signalling pathway in OS development.…”
Section: Discussionmentioning
confidence: 90%
“…Earlier studies have similarly found clear downregulation of Wnt signalling in 25 high-grade prechemotherapy biopsies [36]. In many studies the comparisons are not made between healthy bone and osteosarcoma, therefore not all published gene expression-profiling studies are comparable with ours [37,38]. Therefore, some controversies exist about the involvement of Wnt signalling pathway in OS development.…”
Section: Discussionmentioning
confidence: 90%
“…Decorin had severalfold reduced expression in osteoblastic osteosarcoma patients compared with non-osteoblastic osteosarcoma patients, which could be correlated to a poorer prognosis of the first patient group (80). Immunohistochemistry using polyclonal and monoclonal antibodies against ECM molecules, including decorin, has proved to be a useful tool for the differential characterization of osteoid in a series of 20 osteosarcomas with different variants of osteoid formation (81).…”
Section: Roles In Bone Tumor Progressionmentioning
confidence: 99%
“…In particular, they found significantly modulated the expression of several genes involved in the formation of extracellular matrix, including fibulin-1, already known to be involved in cell morphology modulation, growth and invasion of sarcoma cells (Qing et al, 1997) and suggest that fibulin-1 could be exploited as potential therapeutic target in the future (Kubista et al, 2011).…”
Section: ) Mesenchymal Cancers Osteosarcomamentioning
confidence: 99%